Effect of thermal ageing on the scratch resistance of natural-fibre-reinforced epoxy composites - Ugochukwu, Solomon; M. Ridzuan, M. J.; Abdul Majid, M. S.; Cheng, E. M.; Razlan, Z. M.; Marsi, Noraini (Elsevier, 2021)
In this study, the effects of thermal ageing on the scratch‐resistance properties of natural‐fibre‐reinforced epoxy composites were investigated. Jute, kenaf and hemp‐fibre‐reinforced epoxy composites were fabricated using the vacuum infusion method. The natural‐fibre‐reinforced composites were exposed to thermal ageing for 7, 15, and 30 d at 90 °C temperature. Scratch tests were carried out using a CSM Revetest Xpress machine. The scratch resistance properties, such as the critical normal load, coefficient of friction, penetration depth, fracture toughness, scratch hardness, and scratch tearing were determined after thermal ageing. The results demonstrate that the scratch resistance of the composites decreased as the thermal ageing time increased. However, the jute‐fibre‐reinforced epoxy composites had the highest critical normal load, fracture toughness and scratch hardness compared to those of kenaf and hemp‐fibre‐reinforced epoxy composites after 30 d of thermal ageing.